Concepts and applications of image processing techniques - Salazar, Niceto (Clanrye International, 2015)
The concepts as well as applications of various image processing techniques are elucidated in this comprehensive book. The book offers image processing principles and practical software implementation on a wider area of its usage. It combines the contributions from leading researchers on Applied Digital Image Acquisition and Processing. A crucial characteristic of the book is its focus on software tools and scientific computing in order to enhance results and reach at solutions of different problems.